Clinical changes of multiple sclerosis according to modification of the McDonald criteria. Hospital Almenara, 2001-2015 - Rojas Huerto, Edgard (2019)
Objective. Define if modifications in the McDonald criteria in the last 15 years produced changes in the clinical characteristics and the time of diagnosis of multiple sclerosis. Methods. We revised 91 clinical histories from patients with multiple sclerosis in the last 15 years from the Neurology Service of Hospital Nacional Guillermo Almenara Irigoyen, Lima. We registered clinical and demographical characteristics of the disease. The clinical data were grouped according the date of the diagnosis and McDonald criteria in force at that time: group 1 (2001 to 2005), group 2 (2005 to 2009) and group 3 (2010 to 2015). Results. The average age of the patients was 36,2 years. 51,7% were female. The most common clinical manifestations were motor. 69,23% was a recurrent sender type, 26,37% progressive secondary and 4,40% progressive primary. Disability in recurrent sender type was mild and in the progressive secondary group was moderate. The progressive primary patients had severe disability in group 2 and moderate in group 3. The average disease duration was higher for group 1 and similar in the 2 and 3 groups. Conclusions. The initial manifestations of the disease of patients with multiple sclerosis have not changed during this past 15 years. The predominance of recurrent remitent forms remains the most common but with an increase in progressive primary forms and decrease of progressive secondary group in the last 5 years due to earlier diagnosis of the disease. The time of diagnosis of the disease has decreased in the last 10 years.